Depression and Oropharynx Cancer Outcome. Issue 1 (January 2016) - Shinn, Eileen H.; Valentine, Alan; Jethanandani, Amit; Basen-Engquist, Karen; Fellman, Bryan; Urbauer, Diana; Atkinson, Emma; Yusuf, Syed Wamique; Lenihan, Daniel; Woods, Myrshia L.; Kies, Merrill S.; Sood, Anil K.; et al.
ABSTRACT: Background: Studies have shown a modest relationship between depression and mortality in patients with cancer. Our study addressed methodological weaknesses in the literature by restricting the sample to patients with one cancer type, adjusting for factors known to affect outcome, and following up patients for a sufficient period. Methods: We prospectively followed patients newly diagnosed with squamous cell oropharyngeal cancer from the start of radiation therapy until death or until date of last clinical visit. All patients were optimally treated with radiation and sometimes chemotherapy. After adjusting for tumor stage, treatment, comorbidities, smoking, excessive alcohol use, and demographic factors, we assessed the effects of baseline self-reported depression on overall survival and recurrence. Results: One hundred thirty participants were followed for a median of 5 years. The average age was 56 years, and 83% were male. Eighteen participants died during the study and 15 experienced disease recurrence. Self-reported depression was associated with decreased overall survival duration (hazard ratio = 3.6, 95% confidence interval = 1.2–10.8) and disease recurrence (hazard ratio = 3.8, 95% confidence interval = 1.2–12.2) in multivariate analysis. In addition, smoking was associated with disease recurrence. Conclusions: Patients with oropharyngeal cancer may benefit from depression screening and evidence-based treatments, if appropriate. Future studies are needed to determine whether depression is an independent prognostic factor of outcome and to elucidate biobehavioral mechanisms involved in patients with oropharyngeal cancer. Abstract : Supplemental digital content is available in the text.